Thiophene Disubstituted Benzothiadiazole Derivatives: An Effective Planarization Strategy Toward Deep-Red to Near-Infrared (NIR) Organic Light-Emitting Diodes - Xie, Wentao; Li, Binbin; Cai, Xinyi; Li, Mengke; Qiao, Zhenyang; Tang, Xiaohui; Liu, Kunkun; Gu, Cheng; Ma, Yuguang; Su, Shi-Jian (Frontiers in Chemistry, 2019)
As one of the three primary colors that are indispensable in a full-color display, the development of red emitters is far behind the blue and green ones. Here, three novel orange-yellow to near-infrared (NIR) emitters based on 5,6-difluorobenzo[c][1,2,5]thiadiazole (BTDF) namely BTDF-TPA, BTDF-TTPA and BTDF-TtTPA were designed and synthesized. Density functional theory analysis and photophysical characterization reveal that these three materials possess hybridized local and charge-transfer (HLCT) state feature and a feasible reverse intersystem crossing (RISC) from the high-lying triplet state to the singlet state may conduce to an exciton utilization exceeding the limit of 25% of traditional fluorescence materials under electrical excitation. The insertion of thiophene with small steric hindrance as π-bridge between the electron-donating (D) moiety triphenylamine (TPA) and the electron-accepting (A) moiety BTDF not only results in a remarkable 67 nm red-shift of the emission peak but also brings about a large overlap of frontier molecular orbitals to guarantee high radiative transition rate that is of great significance to obtain high photoluminescence quantum yield (PLQY) in the “energy-gap law” dominated long-wavelength emission region. Consequently, an attractive high maximum external quantum efficiency (EQE) of 5.75% was achieved for the doped devices based on these thiophene π-bridged emitters, giving a deep-red emission with small efficiency roll-off. Remarkably, NIR emission could be obtained for the non-doped devices, achieving an excellent maximum EQE of 1.44% and Commission Internationale de l’Éclairage (CIE) coordinates of (0.71, 0.29). These results are among the highest efficiencies in the reported deep-red to NIR fluorescent OLEDs and offer a new π-bridge design strategy in D-π-A and D-π-A-π-D red emitter design.